Mothulity Facilitates 16S/ITS Amplicon Diversity Analysis. Issue 1 (24th February 2020) - Izak, D.; Gromadka, A.; Kaczanowski, S.
Abstract: We present Mothulity—a novel interface for Mothur, a well‐established tool for 16S/ITS biodiversity analysis. Although Mothur is a well‐documented and virtually complete software suite, its proper execution might be challenging for first‐time users, and editing the Mothur batch scripts is time consuming even for experienced users. Mothur produces little to no graphical output, leaving the generation of plots to the user. Mothulity minimizes the chance of human error through a minimalistic yet powerful interface, with most of the analysis parameters predefined or adjusted automatically. Time spent on running the analysis is drastically reduced, since Mothulity produces an HTML report with publication‐quality figures. Finally, Mothulity can be conveniently used with the SLURM workload manager, and is thereby suitable for a range of computing facilities. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Standard operational procedure (SOP) Basic Protocol 2 : Generating report on pre‐processed data